«Я бережлив… от непривычки к деньгам»: Финансовый аспект командировки и. А. Гончарова на фрегате «Паллада» [“Ia Berezhliv Ot Neprivychki K Den’gam”: The Financial Aspect Of Ivan Goncharov’s Expedition On The Frigate “Pallada”] - Balakin, Alexei (Slavica Revalensia, 2019)
This article tells the story of Ivan Goncharov’s participation in a failed voyage around the world led by vice admiral Yevfimiy Putyatin, with an emphasis on the question of how the future author of The Frigate “Pallada” (1858) profited from his position of Yevfimiy Putyatin’s secretary. Based on a whole set of previously unpublished documents found in the Russian State Navy Archive, the article shows that Goncharov’s assignment was a very lucrative one: not only did he receive a doubled remuneration and generous daily allowances while on board the “Pallada”, but also managed to charge the Russian state for his untimely return from the Eastern coast of Eurasia to Russia proper. All of those documents are published for the first time.